2020
DOI: 10.1111/mcn.13011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary behaviours and weight management: A thematic analysis of pregnant women's perceptions

Abstract: Maternal obesity is associated with increased risk of gestational diabetes and other complications. Although antenatal interventions to help prevent these complications are ongoing, an understanding of overweight and obese pregnant women's opinions and attitudes is lacking. Therefore, this study aims to explore these women's experiences and perceptions of dietary behaviours and weight management during pregnancy. Secondary analysis of qualitative data originally collected to examine lifestyle behaviours in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 52 publications
0
43
0
4
Order By: Relevance
“…Like previous studies, we found that women do not receive adequate or personalized nutrition advice in pregnancy and that it is limited to addressing specific pregnancy issues such as anemia and food safety. 19,20 This may have a negative effect on behavior change as previous studies have found women may be less likely to follow generic advice. 21 In our study, we found that women reported confusion regarding appropriate diet for pregnancy and, worryingly, they felt they could not ask their doctor for clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Like previous studies, we found that women do not receive adequate or personalized nutrition advice in pregnancy and that it is limited to addressing specific pregnancy issues such as anemia and food safety. 19,20 This may have a negative effect on behavior change as previous studies have found women may be less likely to follow generic advice. 21 In our study, we found that women reported confusion regarding appropriate diet for pregnancy and, worryingly, they felt they could not ask their doctor for clarification.…”
Section: Discussionmentioning
confidence: 99%
“…This might have occurred because they believed they would gain weight anyway during pregnancy, so there was no need for a healthy lifestyle. This apparent inconsistency was also found in previous research that reported pregnancy's use as an excuse to indulge [32]. However, some women explained that responsibility for the unborn child was their main reason for being more conscious of their health behaviors [34,32].…”
Section: Discussionmentioning
confidence: 54%
“…This apparent inconsistency was also found in previous research that reported pregnancy's use as an excuse to indulge [32]. However, some women explained that responsibility for the unborn child was their main reason for being more conscious of their health behaviors [34,32]. Overweight women wanted a more uncompromising stance on weight management from maternity care professionals.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Women's partners play a significant role in providing advice and are seen as invaluable support [7]. In addition, the women described how their family, relatives, friends, and health care professionals influenced, for example, healthy food choices [31]. This is an important aspect that should be emphasized in future intervention studies and in practice.…”
Section: Discussionmentioning
confidence: 99%